2008
DOI: 10.1080/10640260802370598
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Experimental Test of the Efficacy of EMDR Treatment on Negative Body Image in Eating Disorder Inpatients

Abstract: Eye Movement Desensitization and Reprocessing (EMDR) therapy is being used by some clinicians to treat eating disorders. Although there is anecdotal and case study data supporting its use, there are no controlled studies examining its effectiveness with this population. This study examined the short and long-term effects of EMDR in a residential eating disorders population. A randomized, experimental design compared 43 women receiving standard residential eating disorders treatment (SRT) to 43 women receiving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 21 publications
2
11
0
1
Order By: Relevance
“…The present study examined the changes in the attachment state of mind, narrative coherence, and reflective function in a sample of AN patients after about a year of EMDR or CBT psychotherapy. The results presented, despite the small sample size, suggest that EMDR is a valuable effective treatment for ED and AN, in line with other clinical study [86]. Several sources starting from 1980 have reported a net correlation between ED and traumatic experiences.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The present study examined the changes in the attachment state of mind, narrative coherence, and reflective function in a sample of AN patients after about a year of EMDR or CBT psychotherapy. The results presented, despite the small sample size, suggest that EMDR is a valuable effective treatment for ED and AN, in line with other clinical study [86]. Several sources starting from 1980 have reported a net correlation between ED and traumatic experiences.…”
Section: Discussionsupporting
confidence: 86%
“…We hypnotize that EMDR method, in respect of other traditional approaches, results in a lower concern and less amount of weight-related thoughts related to body shape, with a consequent improvement on the emotional management and impulses of the patient. It has been suggested that individuals, after EMDR treatments, have lower confusion and apprehension in recognize and answer to emotions and impulses [76,86]. These achievements may contribute to increase the self-esteem and improve the social relations.…”
Section: Discussionmentioning
confidence: 99%
“…These techniques could be incorporated in the standard cognitive behavioural therapy for eating disorders (Tatham, 2011 (Arntz, 2012). In eating disorders, imagery-based interventions such as imagery rescripting (Cooper et al, 2007;NICE, 2005;Pennesi and Wade, 2018) or EMDR (Bloomgarden and Calogero, 2008) seem to be promising in improving body image acceptance and self-compassion and in reducing levels of disordered eating, levels of distress about negative body image memories, and negative emotional self-belief ratings. The results of our study suggest that the imagery-based interventions should not focus exclusively on the past but also on the future to diminish the distress of prospective imagery.…”
mentioning
confidence: 99%
“…With respect to EMDR, a study by Bloomgarden and Colagero investigated effectiveness of EMDR in treating patients with ED (16). There were two groups of patients in this study: the first group of patients received standard residential eating treatment alone (SRT), while the second group was treated with SRT and EMDR therapy combined.…”
Section: Previous Studiesmentioning
confidence: 99%